Implementasi Pendidikan Karakter Pada Mata Pelajaran IPS: Kajian Jenis dan Strategi - Prayoga, Galih; Mustopo Jati, Ibnu; Ferisca, Synthia; Widiasmara, Banu; Wahyu Pratomo, Herdianto (Universitas Insan Budi Utomo, 2024)
study aims to analyze the integration of character education in Social Studies (IPS) learning and effective strategies for its implementation in classrooms. Character education plays a crucial role in shaping students who are not only academically proficient but also possess strong moral and social values. This study employs a literature review method by analyzing previous research on character education in IPS learning. The findings indicate that values such as integrity, cooperation, responsibility, and social awareness can be instilled through project-based learning, group discussions, case studies, and value-based learning methods. Despite challenges in implementation, such as limited time and educators' lack of understanding of effective strategies, appropriate approaches and support from various stakeholders can enhance the effectiveness of character education in social studies.